The Role and Impact of Macrame Business on Women's Economic Empowerment in Lampeji Village, Mumbulsari District - FIRDAUSI, Ifrohatul Dini; PRASETIYORINI, Pudhak; REDJEKI, Sri (PT Keberlanjutan Strategis Indonesia, 2024)
Macrame business in Lampeji Village, Mumbulsari District is one of the alternatives for women's economic empowerment. Macrame is the art of weaving threads that can be made into various products such as bags, wall hangings, and other accessories. Through this business, village women not only get additional income but also skills that improve their quality of life. Rahman, A. & Indriani, T. (2018). The main objective of this study is to determine the role of macrame business in women's economic empowerment in Lampeji Village and how the business can improve the economic welfare of women in Lampeji Village and identify the challenges faced by women in running the macrame business. This study uses a qualitative approach with a case study method. Data were obtained through interviews, direct observation and related documentation. The data analysis technique used is thematic analysis technique to explore information related to the impact of the business on women's economic empowerment. The results of this study are expected to provide insight into the potential of the macrame business as a tool for women's economic empowerment in the village, as well as provide policy recommendations to improve welfare through training, marketing and access to a wider market.